Comparison of child abuse history in patients with and without functional abdominal pain: a case-control study - Seyed Mojtaba Hashemi; Parsa Yousefichaijan; Bahman Salehi; Amir Almasi-Hashiani; Mohammad Rafiei; Sima Zahedi; Esmaeil Khedmati Morasae; Fereshteh Maghsoudlou (BMC Psychiatry, 2020)
Abstract Background Gastrointestinal (GI) disorders are ranked first amongst medical diseases as a trigger of requests for mental health counselling. Child abuse has been regarded as one of the main causes of the development of functional abdominal pain (FAP) in children. This study aimed, therefore, to compare the prevalence of child abuse experience among two groups of patients with and without FAP. Methods A case-control study of children in Arak, Iran, in which experience of child abuse was compared in children with (n = 100) and without functional abdominal pain (n = 100). Three categories of child abuse - emotional abuse, physical abuse, and neglect - were assessed using the Child Abuse Questionnaire. The data were analyzed using Stata software. Results After adjusting for potential confounders, there were group differences in emotional abuse (96% vs. 81%, aOR = 5.13, 95% CI: 1.3–20.3, p = 0.017), neglect (28% vs. 8%, aOR = 4.27, 95% CI: 1.8–11.8, p = 0.001) and total child abuse score (98% vs. 84%, aOR = 8.2, 95% CI: 1.5–43.8, p = 0.014) but not in physical abuse (57% vs. 46%, aOR = 1.47, 95% CI: 0.81–2.60, p = 0.728). Conclusions As the prevalence of child abuse is higher in patients with FAP, child abuse appears to be related to the occurrence of FAP in children. However, the results of this study cannot be generalized to Iranian society generally and further longitudinal studies are recommended.